Miniaturization in percutaneous nephrolithotomy: What is new? - Wei Zhu; Zhicong Huang; Guohua Zeng (Asian Journal of Urology)
Objective: To summarize recent advancements in mini-percutaneous nephrolithotomy (mini-PCNL) in surgical technique, stone removal strategy, lithotripsy, and surgical model from the current literature. Methods: We conducted a narrative review of relevant English-language articles up to October 2022 using the PubMed and Web of Science databases. The following keywords were used in the search: “percutaneous nephrolithotomy”, “minimally invasive percutaneous nephrolithotomy”, “mini-PCNL”, “mini-perc”, “mPCNL”, and “miniaturization”. Results: A series of new progress has been made in many aspects of mini-PCNL, such as further reduction of tract size—needle perc and further improvement of robotic-assisted PCNL—artificial intelligence-powered robotic devices. Conclusion: Many studies and trials have been conducted to reduce morbidity and increase the safety and effectiveness of mini-PCNL. It is crucial to realize that miniaturization of PCNL requires not only a smaller percutaneous tract size, but also an adjustment strategically in renal access, stone removal, lithotripsy, and surgical model in general. More large-scale prospective research needs to be carried out to further validate and optimize the safety and effectiveness of mini-PCNL.